Comparative incidence of footrot in friesian and friesian crosses dairy cattle - Abdullah, A. Salam; Vijchulata, P.; Bahari, S. (Persatuan Doktor Veterinar Malaysia, 1986)

(untitled)
Review of the health record of Friesian and Friesian crosses over a 5 year period showed that more than 80 per cent of [ootrot cases occurred in Friesian. High incidence offootrot correlates well with high rainfall over the area.